Fundamental rights, property and social function: the property’s social function as the foundation of economic, political and social development - pagani, lucas augusto gaioski (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
This present article has the objective to demonstrate the essentiality of Property Rights in the most variable societies, due to its role as a booster to economic, political and social development. Therefore, it is presented the visions of Locke, Hobbes and Hayek regarding property. In a second moment, it wil be presented the definitions for economic, political and social development. Then the Brazilian legislation on the theme is going to be discussed, especially in reference to a social function to be accomplished by the property. It culminates with the definition that societies development depend on the solidification of property as a fundamental institution.